2015
DOI: 10.1111/jph.12380
|View full text |Cite
|
Sign up to set email alerts
|

Species‐Specific PCR‐Based Assay for Identification and Detection of Phomopsis (Diaporthe) azadirachtae Causing Die‐Back Disease in Azadirachta indica

Abstract: Die-back disease caused by Phomopsis (Diaporthe) azadirachtae is the devastating disease of Azadirachta indica. Accurate identification of P. azadirachtae is always problematic due to morphological plasticity and delayed appearance of conidia. A species-specific PCR-based assay was developed for rapid and reliable identification of P. azadirachtae by designing a species-specific primer-targeting ITS region of P. azadirachtae isolates. The assay was validated with DNA isolated from different Phomopsis species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…For analysis of fungal taxa at or below the species level, the more variable ITS region is commonly used (Pryor and Gilbertson ). Sequences of the ribosomal DNA genes, in particular the spacer regions ITS1 and ITS2 surrounding the 5·8S gene have been used to develop specific primers for detection of phytopathogenic fungi (Lee et al ; Iacomi‐Vasilescu et al ; Guillemette et al ; Tapia‐Tussell et al ; Torres‐Calzada et al ; Shankar et al ; Vedashree et al ). This is because ITS regions are of suitable size for PCR amplifications, restriction analysis and sequencing procedures and because ITS regions are variable among species as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For analysis of fungal taxa at or below the species level, the more variable ITS region is commonly used (Pryor and Gilbertson ). Sequences of the ribosomal DNA genes, in particular the spacer regions ITS1 and ITS2 surrounding the 5·8S gene have been used to develop specific primers for detection of phytopathogenic fungi (Lee et al ; Iacomi‐Vasilescu et al ; Guillemette et al ; Tapia‐Tussell et al ; Torres‐Calzada et al ; Shankar et al ; Vedashree et al ). This is because ITS regions are of suitable size for PCR amplifications, restriction analysis and sequencing procedures and because ITS regions are variable among species as well.…”
Section: Resultsmentioning
confidence: 99%
“…radicina with a sensitivity to detect 1 infected seed in 100 carrot seeds (Konstantinova et al ) with seeds incubated for just 1 day. A species‐specific PCR‐based assay was developed and evaluated for its specificity for the identification and detection of P. azadirachtae (Vedashree et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Latent infected D. citri may be the initial source of inoculum of melanose, and a rapid and sensitive diagnosis for detection of this pathogen is currently limited. In previously study, a conserved ITS region was used to design a molecular detection on D. longicolla, D. azadirachtae, and D. sclerotioides [42][43][44][45]. Several studies reported that molecular detection of Diaporthe species from conserved ITS region was weak and poor, thus could not distinguish the Diaporthe complex species [38].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the similar phylogenetic analysis, all of the 140 isolates were identified ( Figure S3). Results showed that D. citri was the predominant species which accounted for Plants 2020, 9, 329 6 of 22 44.3%, following the species of D. eres, D. unshiuensis, D. sojae, D. discoidispora and D. citriasiana, which accounted for 11.4%, 10%, 9.3%, 6.4%, and 3.6%, respectively. There were still 15% isolates that could not be identified to the species level (Supplementary Figure S3).…”
Section: Phylogenetic Analysis Of Diaporthe Speciesmentioning
confidence: 97%
See 1 more Smart Citation